2017
DOI: 10.20302/nc.2017.26.1
|View full text |Cite
|
Sign up to set email alerts
|

Flora and habitats of Vendicari Islet (Isola di Vendicari) in South East Sicily

Abstract: The vascular flora of 'Isola di Vendicari', a small islet (surface 4.45 hectares) located along the Ionian coast of south east Sicily, has been investigated. The surveyed taxa at specific and infraspecific level amount to 80, of which 21 are new records from this islet. The life form spectrum of the current flora brings out the dominance of therophytes as well as a significant occurrence of hemicryptophytes. The plant communities colonizing the surface of the islet have been investigated from floristic, phytos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
(15 reference statements)
1
1
0
Order By: Relevance
“…The brackish rock pools amidst the Crithmo-Staticetea vegetation and the seasonally inundated sediments behind the cliffs are home to a vegetation characterized by Arthrocaulon meridionalis , a succulent chenopod scrub usually linked to seasonally inundated salt marshes, and Limonium virgatum . This vegetation (cluster 11, Table A6 ) is quite similar to the Limonio virgati-Arthrocnemetum macrostachyi , an association belonging to the class Salicornietea fruticosae , described by Biondi et al [ 57 ] from southern Apulia and already reported for Sicily by Minissale and Sciandrello [ 20 ]. Furthermore, on the island, in the hyper-nitrified areas, rarely subject to submersion, a vegetation dominated by Suaeda vera grows, with few other halophilous species, such as Halimione portulacoides , Arthrocaulon meridionalis , Aeluropus lagopoides , Limonium virgatum (cluster 12, Table A6 ).…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…The brackish rock pools amidst the Crithmo-Staticetea vegetation and the seasonally inundated sediments behind the cliffs are home to a vegetation characterized by Arthrocaulon meridionalis , a succulent chenopod scrub usually linked to seasonally inundated salt marshes, and Limonium virgatum . This vegetation (cluster 11, Table A6 ) is quite similar to the Limonio virgati-Arthrocnemetum macrostachyi , an association belonging to the class Salicornietea fruticosae , described by Biondi et al [ 57 ] from southern Apulia and already reported for Sicily by Minissale and Sciandrello [ 20 ]. Furthermore, on the island, in the hyper-nitrified areas, rarely subject to submersion, a vegetation dominated by Suaeda vera grows, with few other halophilous species, such as Halimione portulacoides , Arthrocaulon meridionalis , Aeluropus lagopoides , Limonium virgatum (cluster 12, Table A6 ).…”
Section: Resultssupporting
confidence: 63%
“…As for the small circum-Sicilian islets, they represent sites of high conservation value for the occurrence of several endemic or rare vascular plant species [ 10 , 11 ]. In the past, many of them drove the interest of botanists, which have mainly investigated their vascular floras [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%